Four minutes to save bubblegum pop: Liturgy of bubble gum and the Ten Commandments of political enjoyment (Palimpsesto, 2025)
This article advocates for Bubblegum Pop as an epistemic-political stance, not just as a musical genre. In opposition to academic perspectives that dismiss the superficial, it reclaims pop pleasure as a feminist and queer tool of resistance. From an interdisciplinary perspective—feminist theory, affect studies, and queer approaches—it proposes a manifesto of ten commandments for a sticky politics of pleasure. The practices of Madonna, Britney Spears, Spice Girls, and Lady Gaga are analyzed, as they have used superficiality and aesthetic excess to challenge norms of gender, sexuality, and cultural hierarchies. Bubblegum Pop is presented as a utopian and affective space for the affirmation of marginalized subjectivities. With a performative methodology based on irony, exaggeration, and affectivity, the boundaries between the trivial and the serious are questioned. It is argued that its apparent lightness can operate as a political and revolutionary strategy.
Keywords: Bubblegum Pop; queer theory; politics of pleasure; performativity; camp aesthetics